Iraqi EFL Teachers’ Awareness and Use of Micro and Macro-skills - Kadhim Te'ima, Faris (lark, 2019)
English Language learning and teaching require the mastery of a set of skills from which the four main skills , namely ; listening , speaking , reading and writing .Each one of these four skills has a set of sub-skills which are referred to as micro (minor ) skills and macro(major) skills . Knowledge of these sub-skills is necessary for EFL teachers since the process of teaching and testing English isn’t carried out without having knowledge of these skills .They are thought as indispensible part of the process of English language teaching through which the teachers can set objectives , analyze the lesson , set tests , assign the required time for each activity , etc. To find out the Iraqi EFL language teachers’ awareness and use of micro and macro- skills, an interview and a questionnaire are made to which a sample of Iraqi EFL teachers are exposed . The obtained results show that Iraqi EFL teachers are unaware of the micro and macro skills and almost they don’t use them in teaching .